Education as a weapon of struggle: rethinking the parkland uprising in the age of mass violence - Giroux, Henry A. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This essay attempts to address how the Parkland youth protesters are rewriting the nature of resistance as both an individual and collective effort by creating a new vision of hope and mass struggle. Central to their efforts is an attempt to make education central to politics itself and in doing so they have redefined education as a way of translating personal issues into larger systemic concerns, changing the way people see things, and investing a variety of modes of communication in order to use elements of belief and persuasion as appropriate weapons of struggle. Using new digital technologies and media, these young people are redefining the landscapes of pedagogy and resistance. This paper explores their efforts as a new way to connect politics and education.